Topics in Contemporary Music. Some Archetypal Structural Processes (and TSU) in the Writings and Works of Contemporary Composers - Grabócz, Márta (Res Facta Nova, 2025)
The purpose of this article is to present an astonishing convergence in the creative processes and theories of some contemporary composers on the one hand, and to confront this convergence with TSU theory (Temporal Semiotic Units) on the other. My analyses carried out in the field of electroacoustic music since 1988 have revealed the same broad categories of structuring processes, regardless of the country of origin and the aesthetic conceptions of each creator. The composers in question are the following, according to the chronological order of theorizing their compositional process: F.-B. Mâche, T. Wishart, D. Smalley, C. Miereanu, S. Sciarrino, F. Bayle. After having examined their structural processes, I have drawn up the four main summarizing categories according to their approaches: 1) emergence or beginning; 2) extinction or collapse; 3) culmination point, explosion, or zenithal form; 4) the different cases of “stasis” and stillness, repetitive and discontinuous forms. The archetypal processes of the six composers will be compared to the 19 Temporal Semiotic Units (TSU) established by the composers of Marseille studio of electroacoustic music (GMEM) and of the GRM composers (Paris). This theory has been published in different books and articles in France since 1996. We believe that this view on the convergences of current compositional theories and “temporal semiotic units” provides us with new analytical tools for a better understanding of contemporary musical works.